Nucleophilicity Index Based on Atomic Natural Orbitals - Dariusz W. Szczepanik; Janusz Mrozek (Journal of Chemistry)
A simple method of evaluating a semilocal (regional) nucleophilicity is introduced. The concept involves use of the natural orbitals for atomic populations to identify the most “reactive population” of electrons on particular atom in molecule. The results of test calculations considering the regioselectivity problem in electrophilic aromatic substitution to the benzene derivatives are presented and briefly discussed.